KEBIJAKAN PEMERINTAH TENTANG PENURUNAN TINGKAT PENGANGGURAN DI KOTA MANADO - Lelau, Alfred (HOLISTIK, Journal Of Social and Culture, 2013)
Indonesia as a developing country to this day still cannot be separated from the social problems that gripped the community, especially the socio-economic problems and the problems this government works. For field play an important role in order to protect its people from all socio-economic problems worse excesses, life in society a reality if in the absence of the role of government, the people will give birth to various forms of violence and chaos. The most frightening Scourge of the impact of socio-economic problems is unemployment. Employment issues in Indonesia today has reached a very alarming condition Characterized by the number of unemployed and underemployed large, relatively low incomes and uneven. If the problem is allowed to continue, this will be a "time bomb" Unemployment and underemployment are high is a waste of resources available to families and the public burden, the main source of poverty and Encourage Social Unrest and crime, and could hamper long -term development. Manado as a models of eco-tourism city in the stretcher by the City of Manado, grounded in the economic development of the agricultural sector to the manufacturing industry therefore closely related workforce that will minimize the impact on the unemployment rate. Historical development of ecotourism in Indonesia can be separated in three interrelated stages, each colonial influence, the Conference agreement on biodiversity and ecotourism community development. Unemployment rate in the city of Manado in 2010-2012 that in 2010 the number of unemployed in the city of Manado reached 25 841 inhabitants, in 2011 and 2012 the number reached 24 744 in Manado City pengguran still reached 23.361 inhabitants. The following table of the number of unemployed in Manado City from 2010 to 2012. Keywords: government policy, unemployment